Studi Literatur: Potensi Tanaman Herbal Indonesia sebagai Imunostimulan dan Anti-stress untuk Pencegahan Covid-19 Berbasis Evidence-based Analysis - Meithavia Suciady; Meiliana Meiliana; Dea Nathania Hendryanti (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
World Health Organization has declared COVID-19 as the global pandemic. Strategies to improve the immune system to prevent infection of SARS-CoV-2 virus need to consider physiological and mental health aspects. Many researches have been discovered that various active components in Indonesian herbal plants may have the potential as immunostimulants and anti-stress which can be used as functional foods. This literature study aims to analyze the strength of scientific evidence related to the effect of polar bioactive compounds in various Indonesian herbal plants on the immune system, cytokines activity and the cortisol hormone to decrease the COVID-19 disease risk. The method used was a systematic review (PRISMA) with evidence-based analysis. This study found 7 types of Indonesian herbal plants which have potential to increase the immune system (CD4+ T cell lymphocytes, CD8+, CD25+, CD68+, B cell lymphocytes, NK cells) and immunoglobulin activity (IgA, IgG, IgE, IgM), lower the activity of proinflammatory cytokines (IL-2, IL-4, IL-6, IL-10, IL-12, IL-13, IL-1β, TNF-α, IFN-γ), help manage stress by suppressing the excessive secretion of cortisol and has anti-inflammatory as well as antioxidant properties.